Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4161/cc.11.4.19212
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1-directed, enhanced and aberrant homologous recombination

Abstract: Despite intense studies, questions still remain regarding the molecular mechanisms leading to the development of hereditary breast and ovarian cancers. Research focused on elucidating the role of the breast cancer susceptibility gene 1 (BRCA1) in the DNA damage response may be of the most critical importance to understanding these processes. The BRCA1 protein has an N-terminal RING domain possessing E3 ubiquitinligase activity and a C-terminal BRCT domain involved in binding specific phosphoproteins. These dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 78 publications
(132 reference statements)
1
16
0
Order By: Relevance
“…In particular, aberrations of the Mre11-Rad50-Nbs1 (MRN) complex sensitized cells to PARP inhibition, even in BRCA1-2 wild-type tumors [39]. The potential therapeutic applications of synthetic lethality models could involve the clinical development of PARP inhibitors in the setting of molecularly-driven disease as well as the use of molecules inhibiting specific BRCA1 protein domains [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, aberrations of the Mre11-Rad50-Nbs1 (MRN) complex sensitized cells to PARP inhibition, even in BRCA1-2 wild-type tumors [39]. The potential therapeutic applications of synthetic lethality models could involve the clinical development of PARP inhibitors in the setting of molecularly-driven disease as well as the use of molecules inhibiting specific BRCA1 protein domains [5]. …”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 is also a main component of DNA double-strand break repair through the error-free mechanism of homologous recombination [4]. The pivotal role of BRCA1 in double-strand break repair may be modulated by interaction with other components of homologous recombination [5]. In preclinical models, BRCA1 expression conferred resistance to cisplatin and sensitivity to taxanes [6-10], and its predictive role has been confirmed in several solid tumors, including NSCLC [11-15].…”
Section: Introductionmentioning
confidence: 99%
“…These observations are further supported by results showing decreased survival of irradiated BRCA1 −/− mouse embryonic fibroblasts exposed to IR and emphasize the central role of HRR in the maintenance of genomic integrity. Notably, more recent results suggest that inactivation of BRCA1 ubiquitin-ligase activity up-regulates protein complexes involved in DNA end-resection, causing elevated but aberrant HRR that undermines genomic instability (Drost et al, 2011; Dever et al, 2012). Along these lines, C61G mutation in the BRCA1 gene is associated with complete loss of BRCA1 E3-ubiquitin-ligase function, and disruption of the BRCA1/BARD1 complex, which results in increased formation of RAD51 foci, and abnormal rate of HRR (Drost et al, 2011).…”
Section: Dsb Repair Deficiency and Carcinogenesismentioning
confidence: 99%
“…These Asp/Glu-x-x-4FPhe motifs are quite similar to the pSer-x-x-Phe motif shared by all known BRCA1 (BRCT) 2 -domain binding proteins. 37 Previously oriented SPOT library screens have shown that peptides containing ÎČ -branched and aromatic AAs in the x-x positions show enhanced binding. 13 This preference is also mirrored in many of our sequences.…”
Section: Resultsmentioning
confidence: 99%